Learning from failure in healthcare: Dynamic panel evidence of a physician shock effect - Raf Van Gestel; Tobias Müller; Johan Bosmans (University of Bern, Department of Economics, 2018)
Procedural failures of physicians or teams in interventional healthcare may positively or negatively predict subsequent patient outcomes. We identify this effect by applying (non-)linear dynamic panel methods to data from the Belgian Transcatheter Aorta Valve Implantation (TAVI) registry containing information on the first 860 TAVI procedures in Belgium. We find that a previous death of a patient positively and significantly predicts subsequent survival of the succeeding patient. We find that these learning from failure effects are not long-lived and that learning from failure is transmitted across adverse events.
Keywords: I10; I13; I18; C93; 330; Physician behavior; Learning; Failure